2014
DOI: 10.1007/s10803-014-2281-9
|View full text |Cite
|
Sign up to set email alerts
|

Does Curriculum Matter for Secondary Students with Autism Spectrum Disorders: Analyzing the NLTS2

Abstract: A common presumption of secondary education is that what occurs in-school impacts students after they exit school. Previous researchers found transition-services received in school by students with autism spectrum disorder predicted their post-school success with regards to employment and independent living. This secondary analysis of the National Longitudinal Transition Study-2 sought to understand the relationship between curriculum--functional versus non-functional--and seven measures of post-school outcome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…21 Postsecondary outcomes did not vary by high school urbanicity. 19,21,27 TAY had higher odds of postsecondary employment if their high school contacted a vocational rehabilitation representative during transition planning. 22 However, contact between high schools and postsecondary education institutions (eg, a 2-or 4-year college or vocational and/or technical school) was not a significant predictor of postsecondary education attendance.…”
Section: Institutional Levelmentioning
confidence: 99%
See 2 more Smart Citations
“…21 Postsecondary outcomes did not vary by high school urbanicity. 19,21,27 TAY had higher odds of postsecondary employment if their high school contacted a vocational rehabilitation representative during transition planning. 22 However, contact between high schools and postsecondary education institutions (eg, a 2-or 4-year college or vocational and/or technical school) was not a significant predictor of postsecondary education attendance.…”
Section: Institutional Levelmentioning
confidence: 99%
“…24 Some study authors found a positive relationship between parent income and postsecondary employment, educational attainment, and social engagement, 19, 21, 22, 25 -27, 31, 33, 36 whereas others found no significant association. 19,27,29,34,36,37 Lower parent income was associated with decreased access to services. 30 Parental educational attainment was significantly associated with youth postsecondary education attendance 21,37 and employment 22,25 but not with independent living or friendships.…”
Section: Family Levelmentioning
confidence: 99%
See 1 more Smart Citation
“…In response to the need for better mathematics instruction, many educators in the U.S. and the UK have turned toward evidence-based models and performance standards (Common Core Standards Initiative 2010; Department for Education 2016). While historically students with moderate or severe disabilities have accessed more functional than academic curricula (Bouck and Joshi 2015), there has been increasing emphasis on academic curricula due to ethical and legal expectations regarding students with special educational needs (Barrett et al 1991; Department for Education 2016; U.S. Department of Education 2004). This means that students in special education who could benefit from accessing the general education curriculum should access the same evidence-based educational procedures and be evaluated in respect to the same standards as their peers in mainstream education.…”
Section: Introductionmentioning
confidence: 99%
“…To address expanding interests, curriculum and instruction methodology should remain fluid as students' interests areas evolve. Research emphasizes the importance of educators using curricula that align with students' post-school outcomes but are multi-faceted in nature, to include functional academics, independent living skills, social skills, work experiences, and vocational education (Bouck & Joshi, 2015;Hendricks & Wehman, 2009;Test & Fowler, 2018). The National Technical Assistance Center on Transition (NTACT) has provided lists of evidence-based strategies that are recommended for students with disabilities.…”
Section: Curriculum and Instruction Focused On Specific Post-school Outcomesmentioning
confidence: 99%